(untitled) (Research, Society and Development, 2022)
Objective: To identify the main challenges faced by health professionals during the care of children in the process of hospitalization with suspected or being treated for Covid-19. Methodology: Literature review study, qualitative, descriptive approach, carried out in November and December 2021, in the databases of the Scidentific Electronic Library Online, Latin American and Caribbean Literature in Health Sciences, Online Search and Analysis System of Medical Literature and Google Scholar. For the identification of national and international publications, the following Descriptors in Health Sciences and Medical Subject Headings were selected: “Child/Child”, “Hospitalization/Hospitalization”, “Treatment/Treatment”, “COVID-19”; “Coronavirus Infections/Coronavirus Infections”. Results: After critical reading and analysis of the selected articles, 9 studies were selected as a final sample. Discussion: The process of hospitalization of children with suspicion or for treatment of Covid-19 can be considered something very difficult for the small patient, as they will be temporarily removed from their home, family life, their routine activities. In this context, humanized care together with other care and psychological support can make all the difference. Final considerations: Humanized care together with psychological support can be of great value so that children hospitalized for treatment of Covid-19 do not suffer trauma or trigger possible psychological sequelae due to the hospitalization process.